2021
DOI: 10.1007/s11126-021-09886-y
|View full text |Cite
|
Sign up to set email alerts
|

Receipt of Telepsychiatry and Emergency Department Visit Outcomes in New York State

Abstract: Telepsychiatry has made psychiatric care more accessible to emergency department (ED) patients. To date, most telepsychiatry studies have focused on specific populations or small groups of EDs. This study sought to examine the potential role of telepsychiatry across a wider range of EDs by comparing visit dispositions for psychiatric visits in EDs that did (versus did not) receive telepsychiatry services. ED telepsychiatry service status was identified from the 2016 National ED Inventory-USA and then linked to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Prior research observed that the receipt of telepsychiatry in the ED was associated with improved outcomes including reduced time in the ED, less crowding, reduced travel time for physicians, and improved access to onsite psychiatric consultation. 9,10 Patients with BH conditions need coordinated and accessible care across community and hospital settings. Our null results suggest that hospitals need more resources to integrate BH processes in the ED, including licensed psychiatrists or other BH providers, reimbursement mechanisms for telepsychiatry, and increased access to community-based BH care providers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research observed that the receipt of telepsychiatry in the ED was associated with improved outcomes including reduced time in the ED, less crowding, reduced travel time for physicians, and improved access to onsite psychiatric consultation. 9,10 Patients with BH conditions need coordinated and accessible care across community and hospital settings. Our null results suggest that hospitals need more resources to integrate BH processes in the ED, including licensed psychiatrists or other BH providers, reimbursement mechanisms for telepsychiatry, and increased access to community-based BH care providers.…”
Section: Discussionmentioning
confidence: 99%
“…5 These processes have been shown to efficiently identify previously undiagnosed BH problems, 6,7 reduce wait times and time in the ED, and improve access to psychiatric consultation. [8][9][10] The extent to which US hospital EDs have implemented recommended BH processes and whether specific hospital capabilities can support the integration of BH processes within EDs remains unclear. This study aims to understand the extent to which hospital capabilities are associated with greater adoption of BH care processes in ED.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on EDTP published in the past 2 years shows evidence that telepsychiatry implementation is associated with shorter wait times [18 •, 19, 24], increased access [18•, 25•], more discharges to home [21,22], and increased sense of personal safety for providers [25•]. The receipt of EDTP is associated with lower usage of observation services for psychiatric visits, reducing the amount of time spent in the ED, and addressing the longstanding problem of ED crowding [22]. EDTP can also reduce ED LOS for pediatric patients and reduce travel for face-to-face evaluations, saving up to 2.22 h each day for on-call providers [18•].…”
Section: Discussionmentioning
confidence: 99%
“…Zhong and colleagues shed a different light on ED efficiency by assessing the impact of observation visits (stays of 8-48 h) on disposition across a larger cohort of psychiatric visits to EDs with and without EDTPs by linking the 2016 National ED Inventory-USA to psychiatric visits from the 2016 New York State ED Databases/State Inpatient Database [22]. They demonstrated that psychiatric visits in EDTPequipped EDs used less observational services (2.3% of ED visits) compared to those without EDTP capacity (2.7%) with adjusted odds ratio 0.30 and concluded that receipt of EDTP was associated with "lower usage of observation services for psychiatric visits, likely reducing the amount of time spent in the ED and mitigating the ongoing problem of ED crowding" [22]. There is also evidence that the implementation of a virtual patient navigation program in six EDTP-equipped EDs spanning urban and suburban locations across North Carolina, South Carolina, and Georgia decreased the admission rate for patients with mental health outcomes and reduced the number of follow-up encounters involving self-harm diagnosis within 45 days [23 •].…”
Section: The Impact Of Edtp On Patient Outcomesmentioning
confidence: 99%